The Concordat between the Holy See and the Republic of Poland (1993-1998). Main Questions of the Normalization of the Relations between the Catholic Church and the Polish State after the Collapse of Communism - Krukowski, Józef (Annuarium iuris canonici, 2014)
This event is considered in the historical context of political transformations from the communist totalitarian regime to liberal democracy and at the same time from atheistic state based on the hostile separation to the secular one based on the friendly separation. In complains the following issues: 1) notion and classification of concordats, 2) axiological and formal dimension of its conclusion between the Holy See and Poland (1993-1998), 3) compliance Concordat's with the Constitution of Poland, 4) the stabilization function of Concordat, 5) financial clauses